Drug-Resistant Epimutants Exhibit Organ-Specific Stability and Induction during Murine Infections Caused by the Human Fungal Pathogen Mucor circinelloides - Zanetta Chang (American Society for Microbiology, 2019)
ABSTRACT The environmentally ubiquitous fungus Mucor circinelloides is a primary cause of the emerging disease mucormycosis. Mucor infection is notable for causing high morbidity and mortality, especially in immunosuppressed patients, while being inherently resistant to the majority of clinically available antifungal drugs. A new, RNA interference (RNAi)-dependent, and reversible epigenetic mechanism of antifungal resistance—epimutation—was recently discovered in M. circinelloides. However, the effects of epimutation in a host-pathogen setting were unknown. We employed a systemic, intravenous murine model of Mucor infection to elucidate the potential impact of epimutation in vivo. Infection with an epimutant strain resistant to the antifungal agents FK506 and rapamycin revealed that the epimutant-induced drug resistance was stable in vivo in a variety of different organs and tissues. Reversion of the epimutant-induced drug resistance was observed to be more rapid in isolates from the brain than in isolates recovered from the liver, spleen, kidney, or lungs. Importantly, infection with a wild-type strain of Mucor led to increased rates of epimutation after strains were recovered from organs and exposed to FK506 stress in vitro. Once again, this effect was more pronounced in strains recovered from the brain than from other organs. In summary, we report the rapid induction and reversion of RNAi-dependent drug resistance after in vivo passage through a murine model, with pronounced impact in strains recovered from brain. Defining the role played by epimutation in drug resistance and infection advances our understanding of Mucor and other fungal pathogens and may have implications for antifungal therapy. IMPORTANCE The emerging fungal pathogen Mucor circinelloides causes a severe infection, mucormycosis, which leads to considerable morbidity and mortality. Treatment of Mucor infection is challenging because Mucor is inherently resistant to nearly all clinical antifungal agents. An RNAi-dependent and reversible mechanism of antifungal resistance, epimutation, was recently reported for Mucor. Epimutation has not been studied in vivo, and it was unclear whether it would contribute to antifungal resistance observed clinically. We demonstrate that epimutation can both be induced and reverted after in vivo passage through a mouse; rates of both induction and reversion are higher after brain infection than after infection of other organs (liver, spleen, kidneys, or lungs). Elucidating the roles played by epimutation in drug resistance and infection will improve our understanding of Mucor and other fungal pathogens and may have implications for antifungal treatment.